A review of the diagrid structural system for tall buildings. (11th October 2017) - Liu, Chengqing; Li, Qinfeng; Lu, Zheng; Wu, Handan
Summary: Unlike vertical columns of traditional structure, diagrid structural systems for tall buildings have special inclined columns. Due to the inclined columns, a diagrid structural system for tall buildings produces axial force along the column direction under horizontal load, which has the advantage of resisting horizontal wind load and seismic load and gives more freedom to architectural design, so a diagrid structural system for tall buildings becomes an effective new structure style for tall and super‐tall buildings. Theories and tests regarding the diagrid structural system for tall buildings have been intensely researched since the exterior tube of diagrid structural system for tall buildings was first proposed by Torroja in his seminal book. At present, studies for mechanical characteristics, joint form, theories, and tests have been systematized. This paper systematically summarizes existing research achievements of the diagrid structural system for tall buildings and confirms that the structure has larger lateral stiffness and good seismic performance. Based on the favourable performance of concrete‐filled steel tubes, this paper advises the use of concrete‐filled steel tube columns as the columns in diagrid structural systems for tall buildings.